Diario de vida: experiencias, prácticas y saberes del maestro Jorge Guatame como artista creativo y formador de teatro - Guatame Perdomo, Jorge Enrique (Universidad Antonio Nariño, 2023)
This document is the product of the qualitative research project, with aims is to systematize the experiences and knowledge of the teacher Jorge Guatame, to visualize the artistic and pedagogical processes of his life experience.